Generation of Spherical Cellulose Nanoparticles from Ionic Liquid Processing via Novel Nonsolvent Addition and Drying - Jafar Al Hakkak; Warren J. Grigsby; Kalyani Kathirgamanathan; Neil R. Edmonds (Advances in Materials Science and Engineering)
A novel method to prepare spherical cellulose nanoparticles has been developed using imidazolium ionic liquid processing and regeneration from controlled acetonitrile nonsolvent addition and drying. Nanoparticles ranging from 100 to 400 nm have been prepared with high uniformity. Minimisation of moisture via solvent exchange drying led to discrete nanoparticles, whereas the presence of ambient moisture during regeneration contributed to aggregated morphologies. Chemical analyses of the spherical cellulose nanoparticles reveal a high-amorphous cellulose content. Furthermore, the range of particle sizes achieved with acetonitrile nonsolvent fractionation and solvent exchange drying suggest the size and uniformity of nanoparticle distributions reflect the fractionated cellulose weight fractions. This ionic liquid method is simple, energy efficient, and likely to have wide applicability across other biopolymers as well as potential to prepare surface functionalized spherical cellulose nanoparticles.